2021
DOI: 10.1111/ppl.13544
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of late embryogenesis abundant genes and promoters in pearl millet (Pennisetum glaucum L.) for abiotic stress tolerance

Abstract: Late embryogenesis abundant (LEA) genes display distinct functions in response to abiotic stresses in plants. In pearl millet (Pennisetum glaucum L.), a total of 21 PgLEA genes were identified and classified into six groups including LEA1, LEA2, LEA3, LEA5, LEA7, and dehydrins (DHN). Open reading frames (ORFs) of PgLEAs range from 291 bp (PgLEA1-1) to 945 bp (PgLEA2-11) and distributed randomly among the seven chromosomes. Phylogenetic analysis revealed that all PgLEA proteins are closely related to sorghum LE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 80 publications
1
3
0
Order By: Relevance
“…Among these, OsFAR2 was significantly induced under low temperature, salt, drought, and ABA treatments. Previous research revealed that CREs in the promoter region can be bound by regulatory factors, leading to the induction of their expression under abiotic stress [52]. Our analysis found CREs such as ABREs, MBS, and STREs in the OsFAR2 gene promoter, indicating its ability to induce OsFAR2 expression under abiotic stress.…”
Section: Discussionsupporting
confidence: 52%
“…Among these, OsFAR2 was significantly induced under low temperature, salt, drought, and ABA treatments. Previous research revealed that CREs in the promoter region can be bound by regulatory factors, leading to the induction of their expression under abiotic stress [52]. Our analysis found CREs such as ABREs, MBS, and STREs in the OsFAR2 gene promoter, indicating its ability to induce OsFAR2 expression under abiotic stress.…”
Section: Discussionsupporting
confidence: 52%
“…A hallmark of desiccation tolerance is the accumulation of protective late embryogenesis abundant proteins (LEAPs), which may stabilise the correct structure of proteins and membranes during cellular dehydration [ 3 , 12 , 13 ]. In-depth studies and characterisations of LEA protein families have been carried out in various plants such as Arabidopsis [ 14 ], upland cotton [ 15 ], potato [ 16 ], common wheat [ 17 ], tea plant [ 18 ], rice [ 19 ], pearl millet [ 20 ], Sorghum bicolor [ 21 ], legumes [ 22 ], and desert plant Cleistogenes songorica [ 23 ]. An identification and detailed structural and functional analysis of LEA proteins of resurrection plant species R. serbica has not been done yet.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, the expression of ROS scavenging-related and stress-responsive genes was measured in transgenic tobacco under drought and cold stress. Studies have shown that these genes or their homologous genes play roles in ROS scavenging- and stress-related responses [ 51 , 52 , 53 , 54 ]. Overexpression of TaMYC2 could induce the expression of ROS scavenging-related and stress-responsive genes to a certain extent.…”
Section: Discussionmentioning
confidence: 99%